Pengembangan Bahan Ajar untuk Mata Kuliah Pengembangan IPA SD Pada Program Studi PGSD Berbasis Literasi Sains - Mariyani, Anna; Nurlaily, Vivi Astuti; Fauziyah, Puji Yanti; Maidah, Maidah (JURNAL SINEKTIK, 2024)
The research aims to find out: 1). Developing guided inquiry-based learning books; 2). Test the feasibility of teaching materials;. This study uses the methodResearch And Development (R&D) refers to the 4D model by Thiagarajan namely: 1) Define; 2) Design); 3)Development; 4) Disseminate. The development respondents included 2 validators and 1 practitioner in the initial field trial responses, 5 students in the limited-scale main field trial responses, and 20 class students in the operational field trial respondents. The research data used questionnaires, observations, in-depth interviews, and tests which were then developed and investigated whether this method was successfully developed. The results of this study are: 1) product development of teaching materials based on scientific literacy can improve student test results; 2) the results of this teaching material can be applied